The public health emergency medical countermeasures enterprise : innovative strategies to enhance products from discovery through approval : workshop summary - Wizemann, Theresa M.; Stroud, Clare; Altevogt, Bruce M. (The national academies, 2010)
"During public health emergencies such as pandemic influenza outbreaks or terrorist attacks, effective vaccines, drugs, diagnostics, and other medical countermeasures are essential to protecting national security and the public's well-being. The Public Health Emergency Medical Countermeasures Enterprise (PHEMCE--a partnership among federal, state, and local governments; industry; and academia) is at the forefront of the effort to develop and manufacture these countermeasures. However, despite the PHEMCE's many successes, there are still serious challenges to overcome. Government-funded medical research is not always focused on countermeasures for the most serious potential threats, and it is difficult to engage pharmaceutical and biotechnology companies to develop and manufacture medical countermeasures that have a limited commercial market. At the request of the Secretary of the U.S. Department of Health and Human Services and the Assistant Secretary for Preparedness and Response, the IOM held a workshop February 22-24, 2010, to address challenges facing the PHEMCE. Workshop participants discussed federal policies and procedures affecting the research, development, and approval of medical countermeasures and explored opportunities to improve the process and protect Americans' safety and health."